Hidradenitis Suppurativa (Homoeopathy for All, 2022)
Hidradenitis suppurative (HS), also  known as Verneuil’s disease or acne  inversa, and occasionally is spelled  hidradenitis, is a chronic, recurrent,  debilitating disease that presents  with painful, inflamed lesions in the  apocrine-gland–bearing areas of the  body, most commonly the axillary,  inguinal, and anogenital. Although  the name "hidradenitis suppurativa"  implies a suppurative disorder that  primarily involves sweat glands,  increasing knowledge of the  pathogenesis of the condition has led  to the prevailing theory that HS is a  chronic follicular occlusive disease  involving the follicular portion of  folliculopilosebaceous units.
Keywords: Verneuil’s disease; hidradenitis